Kedudukan Akta Notaris Dalam Terjadinya Peralihan Atas Kekayaan Intelektual - I Nyoman Suyatna; Ni Putu Ayu Bunga Sasmita (Talenta Publisher, Universitas Sumatera Utara, 2023)
This study examines the legal position of a notary deed in the transfer of intellectual property and the role of a notary in making a deed of agreement regarding the transfer of intellectual property. This article used normative legal research with statutory and conceptual approaches. The legal materials used are primary and secondary legal materials. Techniques for collecting legal materials using legal literature studies. The legal material analysis technique used in this research is to use descriptive and argumentative techniques. The results of the research show that the position of a notarial deed in various laws and regulations in the field of Intellectual Property states that in the transfer of Plant Variety and Patent Protection is required to be made before a notary. The role of a notary is very important in the process of transferring intellectual property, who has the authority to make an authentic deed as written proof of the transfer of intellectual property rights and has the authority to provide legal counseling to provide a correct understanding of laws and regulations in the field of intellectual property.